2013
DOI: 10.1517/14740338.2013.829036
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac toxicity of some echinocandin antifungals

Abstract: Mean concentrations of ANID and CASP were associated with statistically significant decreases in left ventricular contractility at concentrations that may be achievable in humans after peripheral administration, while MICA caused no change. TEM studies suggest this may be a result of mitochondrial damage. Caution may be warranted with central administration of these agents to patients with preexisting cardiac dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
31
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 25 publications
8
31
0
1
Order By: Relevance
“…Arrhythmias were not described after antifungal drug administration in the Langendorff studies or in our ICU patients (12,13). The effects of echinocandin treatment observed in our in vivo and in vitro studies, in the Langendorff heart studies, and in the published case reports were rapid.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Arrhythmias were not described after antifungal drug administration in the Langendorff studies or in our ICU patients (12,13). The effects of echinocandin treatment observed in our in vivo and in vitro studies, in the Langendorff heart studies, and in the published case reports were rapid.…”
Section: Discussionmentioning
confidence: 55%
“…In agreement with the data on cardiac side effects seen in our ICU patients after echinocandin administration (12) and case reports of hemodynamic instability (19) and pulmonary edema (20) during anidulafungin administration, we found decreased cardiac function after treatment with anidulafungin and caspofungin. Ex vivo cardiotoxicity studies in rats performed with a Langendorff heart model revealed similar findings (13). We searched the FDA Adverse Events Reporting System (FAERS) database and found four cases of arrhythmias and cardiac failure which may also reflect cardiac events after echinocandin administration (21).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations